South African Renal Registry Annual Report 2016 - Davids, M Razeen; Jardine, Thabiet; Marais, Nicola; Jacobs, Julian C (African Journal of Nephrology, 2018)
The fifth annual report of the South African Renal Registry summarises the 2016 data on renal replacement therapy (RRT) for patients with end-stage renal disease (ESRD) in South Africa. In December 2016, the number of patients with ESRD who were treated with chronic dialysis or transplantation stood at 10 257, a prevalence of 183 per million population (pmp). The growing prevalence observed since the registry was established is due mainly to the increasing numbers of patients accessing haemodialysis in the private sector. In the public sector, which serves 84% of the South African population, the prevalence of RRT (68 pmp) has dipped below the level reported for 1994, so that the disparity in access continues to increase. The disparities between provinces remain, with Limpopo and Mpumalanga the most under-served, as do the disparities between ethnic groups, with Blacks being the most under-served group.